Clinical Characteristics and Outcomes of Severe Pneumonia in Children Under 5 Years Old With and Without Adenovirus Infection in Guangzhou - Zheng, Lingling; Liao, Weiyao; Liang, Feng; Li, Kuanrong; Li, Ling; Liang, Huiying (Frontiers in Pediatrics, 2021)
Objectives To identify the differences of clinical characteristics and outcomes of severe pneumonia in children under 5 years old among with and without adenovirus infection. Methods A retrospective cohort study was conducted in three pediatric hospitals in Guangzhou, China. 1595 children under the age of 5 with WHO defined sever pneumonia had adenovirus testing performed during 1 January 2009 and 31 December 2019. Demographics, complications, the first routine laboratory findings, therapeutic records and clinical outcome were collected from electronic medical records. We compared characteristics of children with and without adenovirus infection. Results Adenovirus were detected in 75 (4.7%) of 1595 severe pneumonia children. Cases with adenovirus infection were more likely to be male (74.7% vs 63.0%), older than one year old (78.7% vs 25.1%), but less likely to have mixed virus infections (25.3% vs 92.9%) and combined with cardiovascular disease (12.0% vs 39.7%), and had more abnormal laboratory results than cases without adenovirus infection. Antiviral therapy (4.9%) was rarely used in children with severe pneumonia, but antibiotic therapy (65.3%) was commonly used in severe pneumonia children, especially cases with adenovirus infection (91.9%). Children infected with adenovirus (9.3% vs 2.5%) were also hospitalized longer and had a higher mortality within 30 days of hospitalization. Conclusions Severe pneumonia children under 5 years old with adenovirus infection had more abnormal laboratory findings and more severe clinical outcomes than cases without adenovirus infection. More attention should be focused on the harm caused by adenovirus infection.